Multiple fluorescence-based PCR-SSCP analysis with postlabeling. - Iwahana, H; Adzuma, K; Takahashi, Y; Katashima, R; Yoshimoto, K; Itakura, M

(untitled) (Genome Research, 1995)
Multiple fluorescence-based PCR single-strand conformation polymorphism (MF-PCR-SSCP) with postlabeling was developed. The target sequence was amplified by PCR using unlabeled primers. Free dNTPs were removed from the amplified products by ethanol precipitation. The dNTPs at the 3' ends of the amplified DNA fragments were exchanged with fluorescent dUTPs or ddNTPs using Klenow fragment of DNA polymerase I. The DNA fragments labeled with fluorescent dUTPs or ddNTPs were heat denatured and applied to a nondenaturing polyacrylamide gel set on an automated DNA sequencer with a gel temperature-controlling system. The image data were analyzed by the computer program Genescan 672. By use of MF-PCR-SSCP with postlabeling, seven different single base mutations of the human K-ras oncogene were detected even under one electrophoresis condition.